CARBON MANAGEMENT AND FINANCIAL PERFORMANCE OF QUOTED OIL AND GAS FIRMS IN NIGERIA (Journal of Global Accounting, 2024)
This study ascertained the effect of carbon management on financial performance of listed oil and gas firms in Nigeria for a period of sixteen (16) years spanning from 2008 to 2023.  Specifically, this study examined the effect of carbon emission management, waste disposal management and transport emission management on return on assets. The panel data sets used in this study were obtained from the annual reports and accounts and Nigerian Exchange (NGX) Group fact books for the study period. Ex-post facto research design was employed. The study is anchored on stakeholder theory. Descriptive statistics of the data set was employed to describe the variables using the mean, standard deviation, minimum and maximum values of the data for the study variables. Inferential statistics using Correlated Random Effects and Panel Least Square Regression analysis were applied to test the hypotheses of the study. Data analysis revealed that: carbon emission management has a positive and significant effect on ROA of listed oil and gas firms in Nigeria (β = 1.6036, p = 0.0117); waste disposal management has a positive and significant effect on ROA of listed oil and gas firms in Nigeria (β = 1.4944, p = 0.0153); transport emission management has a positive and significant effect on ROA of listed oil and gas firms in Nigeria (β = 0.0644, p = 0.0313). In conclusion, efficient emissions control, waste management, and transport optimization, contributes directly to profitability, reinforcing the notion that sustainability and financial success are interconnected in today’s business environment. The study recommends that managers in oil and gas firms should implement comprehensive carbon emission reduction strategies, including the adoption of cleaner technologies and energy-efficient equipment
Keywords: Carbon Emission Management; Return on Assets; Transport Emission Management; Waste Disposal Management